2016
DOI: 10.4028/www.scientific.net/msf.877.78
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the Accuracies of Sump Depth Measurements during DC Casting Process of 7050 Alloy

Abstract: Present work was carried out to investigate the measurement accuracy of the sump depth for 7050 billet in direct chill (DC) casting process. Three measuring methods were applied: (i) Al-30wt.% Cu melt was poured into the mold at the steady state of the casting attempting to record the profile of billet sump; (ii) two steel rods were vertically dipped into the centreline and the edge of the billet attempting to measure the distances between the solidus and the free liquid surface in the hot-top; (iii) several o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This paper presents a comprehensive study on the evolution of multi-physical fields and grain structures during DC casting solidification processes, providing a reference and method for the optimization of DC casting processes for large-size aluminum alloy flat ingots. Based on the results and discussions, the following conclusions can be drawn: The finite element model used in this manuscript underwent validation against the temperature and sump profiles measured by Yu et al [ 35 ]. The findings indicated that the model used in this study agrees well with the experimental results.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This paper presents a comprehensive study on the evolution of multi-physical fields and grain structures during DC casting solidification processes, providing a reference and method for the optimization of DC casting processes for large-size aluminum alloy flat ingots. Based on the results and discussions, the following conclusions can be drawn: The finite element model used in this manuscript underwent validation against the temperature and sump profiles measured by Yu et al [ 35 ]. The findings indicated that the model used in this study agrees well with the experimental results.…”
Section: Discussionmentioning
confidence: 79%
“…Yu et al [ 35 ] have conducted temperature and sump profile measurements of 7050 round DC cast ingots with a 300 mm diameter by using thermocouples and pouring Al-30%Cu melt. In order to verify the reliability of the results in this paper, we compared our simulation results with previous experimental measurements and computational results in terms of the temperature distribution and sump profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the observed profile does not represent the solidus isotherm. This is because Zn penetration could not go deeper into the fixed solid network (when dendrite coherency has been achieved or solid fraction is around 0.35-0.5) as only inter-dendritic feeding is possible in the mushy zone [15]. Therefore, the observed Zn profiles represent an isotherm at a rather lower solid fraction than the solidus.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we expect minimum effect from the depressed solidus with Zn addition on the macroscopic profile. However, the result of temperature profiling using thermocouples is reported to have better accuracy [15]. The grain structure observation shown in Fig.…”
Section: Resultsmentioning
confidence: 99%